Probabilistic Finite Element Analysis of Vertebrae of the Lumbar Spine Under Hyperextension Loading - M. M., Rahman; A., Zulkifli; A. K., Ariffin (Universiti Malaysia Pahang, 2011)

(untitled)
The major goal of this study is to determine the stress on vertebrae subjected to hyperextension loading. In addition, probabilistic analysis was adopted in finite element analysis (FEA) to verify the parameters that affected failure. Probabilistic finite element (PFE) analysis plays an important role today in solving engineering problems in many fields of science and industry and has recently been applied in orthopaedic applications. A finite element model of the L2 vertebra was constructed in SolidWorks and imported by ANSYS 11.0 software for the analysis. For simplicity, vertebra components were modelled as isotropic and linear materials. A tetrahedral solid element was chosen as the element type because it is better suited to and more accurate in modelling problems with curved boundaries such as bone. A Monte Carlo simulation (MCS) technique was performed to conduct the probabilistic analysis using a built-in probabilistic module in ANSYS with 100 samples. It was found that the adjacent lower pedicle region depicted the highest stress with 1.21 MPa, and the probability of failure was 3%. The force applied to the facet (FORFCT) variable needs to be emphasized after sensitivity assessment revealed that this variable is very sensitive to the stress and displacement output parameters.